Credit from the monopoly bank - Yvan Lengwiler; Kumar Rishabh (University of Basel, Center of Business and Economics (WWZ), 2017)
We establish that a monopoly bank never uses collateral as a screening device. A pooling equilibrium always exists in which all borrowers pay the same interest rate and put zero collateral. Absence of screening leads to socially inefficient lending in the sense that some socially productive firms are denied credit due to excessively high interest rate.
Keywords: G21; D82; L12; D00; 330; monopoly bank; credit; contracts; screening; pooling; collateral